2019
DOI: 10.3390/molecules24050836
|View full text |Cite
|
Sign up to set email alerts
|

Flavor Profile Evolution of Bottle Aged Rosé and White Wines Sealed with Different Closures

Abstract: Bottle aging is the final stage before wines are drunk, and is considered as a maturation time when many chemical changes occur. To get a better understanding of the evolution of wines’ flavor profile, the flavor compounds (phenolic and volatile compounds), dissolved oxygen (DO), and flavor characters (OAVs and chromatic parameters) of rosé and dry white wines bottled with different closures were determined after 18 months’ bottle aging. The results showed the main phenolic change trends of rosé wines were dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 32 publications
4
10
0
Order By: Relevance
“…In this study, the initial average concentrations of dissolved oxygen in wines prior to bottling were around 1.2-2.2 mg/L, while at the end of storage the concentrations were around 0.4 mg/L (Figure 2). The ranges of dissolved oxygen determined in this study are similar to that reported by other authors (Danilewicz, 2016;Dimkou et a., 2013;Fracassetti et al, 2013;Gambuti et al, 2017, Ling et al, 2019Lopes et al, 2009;Waterhouse et al, 2016). Namely, dissolved oxygen in all wine samples started to decrease immediately after bottling and was consumed in the majority of the treatments in the first three months of aging.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…In this study, the initial average concentrations of dissolved oxygen in wines prior to bottling were around 1.2-2.2 mg/L, while at the end of storage the concentrations were around 0.4 mg/L (Figure 2). The ranges of dissolved oxygen determined in this study are similar to that reported by other authors (Danilewicz, 2016;Dimkou et a., 2013;Fracassetti et al, 2013;Gambuti et al, 2017, Ling et al, 2019Lopes et al, 2009;Waterhouse et al, 2016). Namely, dissolved oxygen in all wine samples started to decrease immediately after bottling and was consumed in the majority of the treatments in the first three months of aging.…”
Section: Resultssupporting
confidence: 90%
“…During bottle aging, wine is exposed to relatively small amounts of oxygen, but even these concentrations are sufficient to impact the outcome of aging process (Ugliano, 2013). In this study, the average concentrations of dissolved oxygen in wines prior to bottling were around 3.3-4.0 mg/L, while at the end of storage the concentrations were in range from 0.2 to 0.5 mg/L, which is similar to those found in other studies (Danilewicz, 2016;Dimkou et a., 2013;Fracassetti et al, 2013;Gambuti et al, 2017, Ling et al, 2019Lopes et al, 2009;Waterhouse et al, 2016). Immediately after bottling, a rapid decrease of dissolved oxygen can be observed in all treatments in the first three months of aging ( Figure 3).…”
Section: Resultssupporting
confidence: 88%
“…Wine aroma is produced by the interactions of hundreds of chemical compounds derived from multiple sources [ 1 ]. According to their origin, wine aroma compounds can be grape-derived such as monoterpenes and norisoprenoids [ 2 , 3 ]; microbially-derived secondary metabolites formed from sugar and amino acid metabolism during the fermentation [ 1 , 4 ]; and those compounds formed during wine storage, either in oak barrels [ 5 , 6 ] or in bottles [ 7 , 8 ]. The major groups of aroma compounds are monoterpenes, norisoprenoids, aliphatics, higher alcohols, esters, phenylpropanoids, methoxypyrazines, and volatile sulfur [ 2 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Wine aroma slightly evolves during bottle aging because the amounts of oxygen that penetrate through the closures are low [ 7 , 10 , 11 ]. Oxygen penetrates through the stoppers at a rate between 0.005 and 5 mg L −1 year −1 [ 12 ], depending on the type of closure used [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation